ECOLOGICAL-ECONOMIC FEASIBILITY OF USE OF MATERIALS OF SECONDARY PROCESSING IN HOUSING SECTOR WITHIN THE PROGRAM OF RENOVATION - E. Zimin (Вестник университета)
In the present article we show the necessity and possibilities of the recycling of construction materials used in the sphere of housing and public utilities. Large-scale programme of housing renovation taking place in Moscow is going to leave behind a lot of construction waste. The article presents the ways of dealing with the demolition waste, such innovative types of its utilization as recycling, regeneration and recovery are described along with the ways of secondary materials’ usage.